2015
DOI: 10.1097/sap.0000000000000627
|View full text |Cite
|
Sign up to set email alerts
|

An Updated View of the Integrated Plastic Surgery Match

Abstract: Integrated plastic surgery residency programs continue to be highly competitive, with overall increasing research experience, but slightly lower Step 1 scores and AOA membership than that in previous years. If the trend of decreasing independent and increasing integrated positions continues, the applicant only interested in plastic surgery may find the integrated pathway a more feasible option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Numbers of research experiences and publications have been shown to be higher among matched applicants in the integrative plastic surgery program versus unmatched applicants . Although research experience is considered by many to be an integral factor to matching in otolaryngology, no prior studies have shown that medical student research increases the odds of matching in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of research experiences and publications have been shown to be higher among matched applicants in the integrative plastic surgery program versus unmatched applicants . Although research experience is considered by many to be an integral factor to matching in otolaryngology, no prior studies have shown that medical student research increases the odds of matching in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated plastic surgery applicants consistently have historically reported some of the highest mean numbers of publications, abstracts, and research experiences among graduating medical students, and their research productivity has only continued to rise. 1 , 4 , 8 The mean number of publications authored by matched plastic surgery applicants has increased considerably over the last decade (3.4 in 2007 versus 14.2 in 2018). 3 , 6 However, a 2006 study reported that, while applicants with one or more publications received significantly more interview invitations than those with none, the quantity of an applicant’s publications did not correlate with the number of interview invitations.…”
Section: Objective Factorsmentioning
confidence: 99%
“…From 2007 to 2019, the number of integrated plastic surgery residency positions increased from 92 to 172. 5 Simultaneously, the number of independent plastic surgery residency positions available through the San Francisco Match reached historic lows, decreasing from 93 to 63. 6…”
Section: Historymentioning
confidence: 99%